Between the sacred and the profane: the figure of the maγeipoς in ancient Greece - García Soler, María José (ARYS. Antigüedad: Religiones y Sociedades, 2020)
The term μάγειρος is used in ancient Greece to designate a complex character. Originally it was the officer in charge of sacrifices to kill the victim and then once removed a section dedicated to the gods, the sacrificial meal cooked for. From this second function, and with the extensión of the new gourmet refinements, has specialized as professional cook hired for the preparation of a banquet on the occasion of celebrations of various kinds. In this way there was a progressive shift of public to private and religious to the profane, until the μάγειρος was identified properly by a cook and not by a sacrificer.